A CROSS-CULTURAL ANALYSIS ON THE PRACTICE OF SUSTAINABLE UNIVERSITY INITIATIVES - Efendi, David; Swarga, Alim Bubu; Mudzakkir, Moh.; Bustami, Mohammad Reevany; Nasruddin, Ellisha (UI Scholars Hub, 2023)
Climate change and other environmental problems have become a global concern. Intrinsically, this creates higher education institutions such as Universitas Muhammadiyah Yogyakarta (UMY) and Universiti Sains Malaysia (USM) taking part in various green campus measurements to address this problem. This study analyzes the factors of how higher education institutions such as UMY and USM initiate green campuses and sustainable universities. It assumes these two universities align with the implementation of green campus initiation despite their different university status. This research is qualitative research using a comparative study between UMY and USM. This research data uses interviews from the university website, especially university leaders and all related stakeholders, and secondary data such as relevant documents and articles related to this study. Therefore, in this study, the authors use the framework theory of planned behavior, which systematically analyzes the factors that influence the behavior of stakeholders, especially university leaders, by looking at three factors: environmental motive and concern, educational university programs, and promotional activities. By employing planned behavior analysis, it was found that both universities have initiated to become green campuses by implementing various programs and collaborating with stakeholders such as Non-Governmental Organizations (NGOs), communities, and other academic communities. In addition, participating in green campus measurements demonstrates the role of UMY and USM in contributing to good university governance. It reflects their role as universities in mitigating the impact of climate change caused by using non-environmentally friendly energy and waste. All in all, the two universities, UMY and USM, have vital initiatives in the practice of sustainable university.